THE USE OF VISUALIZATION AUDITORY KINESTETIC (VAK) MODEL WITH MULTIMEDIA IN IMPROVING IPS LEARNING OUTCOMES ABOUT INDONESIAN INDEPENDENCE PROCLAMATION IN GRADE V STUDENTS OF SD NEGERI 1 SUROTRUNAN OF TEACHING YEAR 2016 / 2017 - Malik, M Romaryo Molana; Chamdani, Muhamad; Suyanto, Imam (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The use of Visualization Auditory Kinestetic (Vak) Model with Multimedia in Improving IPS Learning Outcomes About Indonesian Independence Proclamation In Grade V Students of SD Negeri 1 Surotrunan of Teaching Year 2016 / 2017. The purpose of this study is to improve the learning outcomes of IPS about the proclamation of Indonesian independence. This study is a collaborative action study (PTK). The subjects of this study are teachers and students of class V, amounting to 23 students. Data collection techniques in research, are observation, interviews, and tests. Data validity was using source triangulation and engineering triangulation. Data analysis was using data reduction, data presentation, and conclusion. The results showed that the application of Visualization Auditory Kinestetic (VAK) model with multimedia can improve IPS learning result.Keywords: Kinestetic Visualization Auditory, multimedia, IPS learning outcomes